Homely Town. Moin Housing Model - Sanabria Hidalgo, Fabiola (2017)
This academic project recreates a housing model of tropical or Caribbean architectural typology; located in an area of great port development, on the eastern coast of Costa Rica. Wood is the main material used in its structural system.